Pharmacological Basis for Antispasmodic, Bronchodilator, and Antidiarrheal Potential of Dryopteris ramosa (Hope) C. via In Vitro, In Vivo, and In Silico Studies - Iram Iqbal; Fatima Saqib; Muhammad Farhaj Latif; Hamna Shahzad; Dima Lorena; Bayan Sajer; Manea Rosana; Pojala Ciprian; Necula Radu Dan (ACS OMEGA, 2023)
Background: Dryopteris ramosa is used as an old treatment for several diseases. D. ramose fronds are eaten to treat gastrointestinal (GIT) issues and as an antibiotic. However, there is a dearth of literature justifying its traditional use. Aims and objectives: the current work used biological and molecular docking studies to support traditional usage and elucidate D. ramosa’s multitarget mechanism. Materials and methods: Bioactive compounds were docked in silico. Force displacement transducers coupled with a power lab data gathering system examined the effects of compounds on rabbit jejunum, trachea, and aorta tissues. Albino mice and rats were used for in vivo studies. Results: Bioactive compounds interacted with inflammation, asthma, and diarrhea genes, according to in silico studies. D. ramosa crude extract (Dr.Cr) calmed impulsive contractions and K+ (80 mM)-provoked contractions in the jejunum and tracheal tissue dose-dependently, showing the presence of the Ca++ channel-blocking (CCB) effect, further verified by the rightward parallel shift of CRCs equivalent to verapamil. Polarity-based fractionation showed spasmolytic activity in Dr.DCM and muscarinic receptors mediated spasmogenic activity in the Dr.Aq fraction. Dr.Cr vasoconstricted the aortic preparation, which was totally blocked by an angiotensin II receptor antagonist. This suggests that Dr. Cr’s contractile effect is mediated through angiotensin receptors. In rats and mice, it showed anti-inflammatory and antidiarrheal action. Conclusion: This study supports the traditional medicinal uses of D. ramosa against GIT disorders and may be an important therapeutic agent in the future.
Keywords: Bioactive compounds; Bioactive compounds Carbohydrates Flavonoids Ligands; Plants